The Evaluation Of Peo Attainment Based On Alumni And Employer Survey - Ahmad , Arfah; Ahmad, Suziana; Hashim, Mohd Ruzaini; Kasdirin, Hyreil Anuar (2011)
This study is to investigate the evaluation of Program Educational Objectives (PEO) attainment in Faculty of Electrical Engineering (FKE). The PEO for this facuIty consists of five statements that describe expected achievements of graduates in their career and professional life a few years after graduation. Method used to measure the achievement of each PEO is based on alumni survey and employer survey that involve all the alumni in this faculty graduated since 2005 and their employers. The attainment for each PEO is based on the measurement of continuous quality improvement items placed in both questionnaires. Results shows that, out of five PEO listed, only one, that is PEO 3 is not achieve.